Phase comparison protection for distribution networks with high PV penetration - Alvin T.G.M.; Abidin I.Z.; Hashim H.; Abidin A.A.Z. (IEEE Computer Society, 2023)
With the availability and reduced cost of renewable energy sources such as Solar PV, distributed generation (DG) becomes an increasingly common practice in harnessing these energy sources. However, a high level of penetration of the energy sources in the distribution network will cause issues such as reverse power flow and the disruptions to the coordination of existing protection system. This paper looks on how reverse power flow will affect the tripping times of overcurrent relays and its effect on the coordination of the protection system. This paper also investigates on the possibility of using the phase comparison protection method to improve the coordination of the protection system in a high PV penetration environment. © 2014 IEEE.